Avaliação do(s) modelo(s) educacional(is) de formação desenvolvido(s) para a atenção à saúde materno-infantil em Sobral/CE no período de 2014 a 2018 - Nogueira, Denise Lima (2021)
In Collective Health, both health care and education are social practices. Thus, the way in which they dialogue and interrelate influences the organization of health services. In Brazil, Health Care Networks emerge as a strategy to overcome the fragmentation of health care and improve the political and institutional functioning of the Unified Health System (SUS). In 2011, the Ministry of Health, aiming to guarantee quality assistance to women from reproductive planning to the puerperium and to children from birth to 24 months of age, established the Stork Network. Nevertheless, understanding that ensuring quality care for women during pregnancy and childbirth and for children, within the scope of SUS, requires professionals to develop skills that allow the provision of health care based on the principles of integrality and universality, this research aimed: to evaluate the educational models of training for maternal and child health care in the Sobral/CE region, within the scope of the Stork Network. Therefore, an evaluative, qualitative, case study research was carried out in Sobral/CE, from June 2019 to March 2020, having as units of analysis documents, field diary and interviews with participants, through theoretical sampling and triangulation of the data. The documents included those related to the educational processes on maternal and child health care from 2014 to 2018. Participants comprised 14 people, including managers / coordinators of health care and education in Sobral/CE and Ceará and health services maternal and child health in Sobral/CE. Documentary collection took place using a pre-defined instrument and the interview was semi-structured and recorded. The information from the interviews was organized and analyzed based on the thematic content analysis of Bardin, with support from the MAXQDA Analytics Pro 2000 software, and the documentary information analyzed through the documentary analysis, to which the information from the field diary was added. The research was approved by the Research Ethics Committee of the Federal University of Ceará, under protocol number 3,355,553. The results of the data sources were presented and discussed organically. These were organized into two categories of analysis, which were divided into subcategories, converging in the elaboration of a proposed intervention modeling. The categorization “The Stork Network in the municipality of Sobral, Ceará, Brazil” was divided into three other analysis subcategories and the category “The Training Processes in and for Maternal and Child Health Care in Sobral, Ceará, in 10 the period of 2014 to 2018” was divided into six other subcategories. Based on the results of the two analysis categories, we present a proposal for a Logical Model of Training for Maternal and Child Health Care in the municipality of Sobral/CE, within the scope of the Stork Network in order to contribute to the understanding, on the part of the actors involved, the articulation of the elements and activities of this to obtain the programmed results, as well as to guide decision making. That said, this research allowed us to conclude that training practices are one of the strategies adopted for the qualification of maternal and child health care in Sobral/CE.